Lightweight Fe3C@Fe/C nanocomposites derived from wasted cornstalks with high-efficiency microwave absorption and ultrathin thickness - Qi, Guangyu; Liu, Yuan; Chen, Lili; Xie, Peitao; Pan, Duo; Shi, Zhicheng; Quan, Bin; Zhong, Yiming; Liu, Chunzhao; Fan, Runhua; Guo, Zhanhu (Advanced composites and hybrid materials, 2021)
As a typical lightweight material, carbon materials have great application prospects in fabricating microwave absorbers. In this work, the Fe 3 C@Fe/C composites with porous microstructure are obtained by a simple and environmentally friendly method with wasted cornstalks as raw materials. The reflection loss of absorbing composites reaches the minimum value which is less than −50 dB when the thickness is 1.13 mm, while widest effective absorbing bandwidth reaches 5.1 GHz when thickness is 1.50 mm. The stalk-made nanocomposites’ excellent absorbing ability is mainly credit to excellent impedance matching and attenuation characteristics of composites, which is further credit to a synergistic influence of the dielectric loss from the multiple interfaces in porous microstructure and magnetic loss from iron nanoparticles. A low-cost method to obtain microwave absorption materials and realize high-value utilization of agricultural waste to reduce pollution caused by burning cornstalks is put forward. Graphic Abstract